Enhancing Doxorubicin Efficacy in Hepatocellular Carcinoma: The Multi-Target Role of Muscari comosum Extract - Alessandro Pistone; Ilenia Matera; Vittorio Abruzzese; Maria Antonietta Castiglione Morelli; Martina Rosa; Angela Ostuni (Applied Sciences)
Hepatocellular carcinoma (HCC) is still a leading cause of cancer-related mortality worldwide, characterized by poor prognosis and limited therapeutic efficacy of conventional chemotherapeutics such as doxorubicin. Phytochemicals are promising adjuvants in cancer therapy due to their multi-targeted effects. In this in vitro study, we investigated the impact of a methanol–water extract (70:30 v/v, MET70) from Muscari comosum bulbs, rich in polyphenols and flavonoids, on doxorubicin-treated HepG2 human hepatoma cells. Co-treatment with MET70 increased intracellular reactive oxygen species (ROS) associated with downregulation of Nrf2 signaling, suppression of antioxidant enzymes (SOD2, GPX-1) and decreased mitochondrial UCP2 expression. MET70 modulated the inflammatory response induced by doxorubicin by decreasing TNF-α and increasing IL-6 expression. MET70 also promoted protein homeostasis through PDIA2 upregulation without exacerbating endoplasmic reticulum stress and inhibited autophagy by reducing Beclin-1 levels, contributing to increased chemosensitivity. Moreover, MET70 downregulated ABCC1 expression, suggesting a role in overcoming multidrug resistance. All these findings demonstrate that Muscari comosum extract enhances doxorubicin efficacy by targeting redox balance, inflammatory signaling, autophagy, and drug resistance, offering a promising redox-based strategy for improving HCC therapy. However, further studies should be performed in vivo.